Embodying Ecological Policy in Defending the Leuser Ecosystem Area for Sustaining Collective Life - Triono Eddy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This work is aimed at exploring an appropriate strategy and approach in embodying the ecological policy in defending the Leuser ecosystem area for maintaining the sustainability of collective life.